Spectral Precoding Integration in OTFS Modulation - Vahid Vahidpour; R. López-Valcarce (IEEE Wireless Communications and Networking Conference, 2025)
Practical Orthogonal Time-Frequency-Space (OTFS) systems face excessive out-of-band radiation (OBR), which degrades overall network performance. We investigate the application of spectral precoding to cyclic prefix-based OTFS to mitigate OBR in high-mobility wireless channels, and propose a modification of the low-complexity delay-time domain maximal ratio combining iterative decoder to account for the spectral precoding operation at the transmitter. Simulation results demonstrate the effectiveness of the proposed scheme to mitigate OBR and improve bit error rate, showcasing its potential for high-mobility OTFS applications.
Keywords: mayte; multicarrier communications; OTFS; spectrum shaping